Variations in the organisation of and outcomes from Early Pregnancy Assessment Units: the VESPA mixed-methods study - Maria Memtsa; Venetia Goodhart; Gareth Ambler; Peter Brocklehurst; Edna Keeney; Sergio Silverio; Zacharias Anastasiou; Jeff Round; Nazim Khan; Jennifer Hall; Geraldine Barrett; Ruth Bender-Atik; et al. (National Institute for Health Research, 2020)
Background: Early pregnancy complications are common and account for the largest proportion of emergency work in gynaecology. Although early pregnancy assessment units operate in most UK acute hospitals, recent National Institute of Health and Care Excellence guidance emphasised the need for more research to identify configurations that provide the optimal balance between cost-effectiveness, clinical effectiveness and service- and patient-centred outcomes [National Institute for Health and Care Excellence (NICE). Ectopic Pregnancy and Miscarriage: Diagnosis and Initial Management. URL: http://guidance.nice.org.uk/CG154 (accessed 23 March 2016)]. Objectives: The primary aim was to test the hypothesis that the rate of hospital admissions for early pregnancy complications is lower in early pregnancy assessment units with high consultant presence than in units with low consultant presence. The key secondary objectives were to assess the effect of increased consultant presence on other clinical outcomes, to explore patient satisfaction with the quality of care and to make evidence-based recommendations about the future configuration of UK early pregnancy assessment units. Design: The Variations in the organisations of Early Pregnancy Assessment Units in the UK and their effects on clinical, Service and PAtient-centred outcomes (VESPA) study employed a multimethods approach and included a prospective cohort study of women attending early pregnancy assessment units to measure clinical outcomes, an economic evaluation, a patient satisfaction survey, qualitative interviews with service users, an early pregnancy assessment unit staff survey and a hospital emergency care audit. Setting: The study was conducted in 44 early pregnancy assessment units across the UK. Participants: Participants were pregnant women (aged ≥ 16 years) attending the early pregnancy assessment units or other hospital emergency services because of suspected early pregnancy complications. Staff members directly involved in providing early pregnancy care completed the staff survey. Main outcome measure: Emergency hospital admissions as a proportion of women attending the participating early pregnancy assessment units. Methods: Data sources - demographic and routine clinical data were collected from all women attending the early pregnancy assessment units. For women who provided consent to complete the questionnaires, clinical data and questionnaires were linked using the women's study number. Data analysis and results reporting - the relationships between clinical outcomes and consultant presence, unit volume and weekend opening hours were investigated using appropriate regression models. Qualitative interviews with women, and patient and staff satisfaction, health economic and workforce analyses were also undertaken, accounting for consultant presence, unit volume and weekend opening hours. Results: We collected clinical data from 6606 women. There was no evidence of an association between admission rate and consultant presence (p = 0.497). Health economic evaluation and workforce analysis data strands indicated that lower-volume units with no consultant presence were associated with lower costs than their alternatives. Limitations: The relatively low level of direct consultant involvement could explain the lack of significant impact on quality of care. We were also unable to estimate the potential impact of factors such as scanning practices, level of supervision, quality of ultrasound equipment and clinical care pathway protocols. Conclusions: We have shown that consultant presence in the early pregnancy assessment unit has no significant impact on key outcomes, such as the proportion of women admitted to hospital as an emergency, pregnancy of unknown location rates, ratio of new to follow-up visits, negative laparoscopy rate and patient satisfaction. All data strands indicate that low-volume units run by senior or specialist nurses and supported by sonographers and consultants may represent the optimal early pregnancy assessment unit configuration. Future work: Our results show that further research is needed to assess the potential impact of enhanced clinical and ultrasound training on the performance of all disciplines working in early pregnancy assessment units. Trial registration: Current Controlled Trials ISRCTN10728897. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 46. See the NIHR Journals Library website for further project information.